إدارة صندوق األجرة يف منتج التأمني التكافيل الوقف من منظور مقاصد الرشيعة بيوجياكرتا - Setiawan Bin Lahuri Lahuri; Fadhila Tianti Mudi Awalia Awalia; Muhammad Alfi Syahrin Syahrin (Islamic Economics Journal, 2020)
This study aims to discuss how the management of the ujrah funds on the waqf takafulink product and the management of the ujrah funds in the perspective of maqasid shariah in presenting wealth benefits. To achieve the discussion's objectives, researchers used field research with qualitative research types and a case study approach. As for collecting data, researchers conducted observations,interviews and looked at existing documents. Meanwhile, in analyzing the problem, the researcher used a qualitative descriptive technique and a maqasid shariah approach technique, so that this study could explain in detail about the management of funds in the waqf takafulink product. The results found the management of ujrah funds on the waqf takafulink product was contrary to the principles of sharia insurance because of the transfer of participant rights for the benefit of others as seen from the imposition of theujrah funds that charged to participants to finance operations. But if the tax is on the company's amount of assets, the company should be able to bear the company’s operating costs without burdening the participants. Whereas from the review of maqasid shariah, the management of ujrah funds on takafulink products, waqf greetings is also against justice and benefit, because in managing funds there is an element of tyranny, and the status of ownership of property transferred in a way that is not in line with Islamic law.